2019
DOI: 10.1016/j.expneurol.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Dim light at night impairs recovery from global cerebral ischemia

Abstract: Nighttime lighting is one of the great conveniences of modernization; however, there is mounting evidence that inopportune light exposure can disrupt physiological and behavioral functions. Hospital patients may be particularly vulnerable to the consequences of light at night due to their compromised physiological state. Cardiac arrest/cardiopulmonary resuscitation (CA) was used to test the hypothesis in mice that exposure to dim light at night impairs central nervous system (CNS) recovery from a major patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 62 publications
(91 reference statements)
2
28
3
Order By: Relevance
“…Indeed, many of the negative consequences of the ICU for health outcomes have historically been attributed to disrupted sleep. Our studies of nocturnal mice (that typically sleep during the light phase) demonstrate that although sleep is a highly salient output of circadian clocks, disruption of the central circadian clockwork is sufficient to produce poor outcomes (Alibhai et al., 2014; Fonken et al., 2019; Penev et al., 1998). Further, we have previously shown that sleep is not disrupted by dim light at night in house mice (Borniger, Weil, Zhang, & Nelson, 2013) indicating that sleep disruption is unlikely to drive the current phenomenon.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, many of the negative consequences of the ICU for health outcomes have historically been attributed to disrupted sleep. Our studies of nocturnal mice (that typically sleep during the light phase) demonstrate that although sleep is a highly salient output of circadian clocks, disruption of the central circadian clockwork is sufficient to produce poor outcomes (Alibhai et al., 2014; Fonken et al., 2019; Penev et al., 1998). Further, we have previously shown that sleep is not disrupted by dim light at night in house mice (Borniger, Weil, Zhang, & Nelson, 2013) indicating that sleep disruption is unlikely to drive the current phenomenon.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the survival of penumbral tissue is a determinant of long‐term functional outcomes and supporting the survival of those cells is a major goal of ischaemia research (Rogers, Campbell, Stretton, & Mackay, 1997). Recently, we reported that artificial dim light at night exacerbates the cell death and inflammatory responses to cardiac arrest and cardiopulmonary resuscitation, a global ischaemic injury (Fonken et al., 2019). Here, we hypothesized that exposure to dim white light, at night during the period after experimental focal ischaemic stroke would increase infarct size, exacerbate inflammatory responses and impair functional outcomes compared to animals housed in dark night conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, people are gradually realizing the ill effects of night-time light exposure and considering it as an environmental perturbation [ 5 , 6 ]. Recent studies have indicated that alteration of daily light dark cycle contributes to the development of many pathophysiological conditions such as cardiovascular disease [ 7 , 8 ], metabolic syndrome [ 9 , 10 ], sleep disorders [ 11 ], aging [ 12 ], neurodegenerative disorders [ 13 , 14 , 15 ], mood disorders [ 16 ], and cognitive impairment [ 17 ]. Exposure to artificial lighting during the night (dim light at night (dLAN)) and shift working are reported to interfere with proper physiological functioning of the brain and body [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circadian disruption in response to diverse environmental or endogenous perturbations can misalign metabolic homeostasis and thereby contribute to the development of metabolic disorders [ 18 , 19 , 20 ]. Accordingly, a growing number of epidemiological and experimental studies have reported an association between dLAN exposure and metabolic dysfunction, leading to an increased risk of obesity [ 21 , 22 ], type 2 diabetes mellitus [ 23 ], and cardiovascular disease [ 24 , 25 ]. Experiments in mice showed that dLAN (5 lx) exposure resulted in an impaired glucose tolerance and increased body mass, likely due to shifting the rhythm of food intake into daytime [ 26 ].…”
Section: Introductionmentioning
confidence: 99%